Off-host Study on Use of Bacterial Biocontrol Agents against Ruminant Tick Rhipicephalus microplus under Field Conditions - Jadhav, Balaji S.; Narladkar, Babasaheb W.; Gudewar, Jagdish G.; Chigure, Gajanan M. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
In an off-host study, bacterial biocontrol agents, viz., Bacillus thurinngiensis var kurstaki, Bacillus thuringiensis var kurstaki toxin (Dipel8L), Bacillus thuringiensis var israelensis, Bacillus weihenstephanensis var WSBC and Bacillus weihenstephanensis var KBAB4 were evaluated against Rhipicephalus (Boophilus) microplus ticks. All four bacteria and one toxin were evaluated at five different concentrations. The LC50 values of one toxin and three bacteria, viz., Bacillus thuriengiensis var krustakivar (Dipel 8L) toxin, Bacillus thuriengiensis var kurstaki, Bacillus thuriengiensis var isaralensis and Bacillus weihenstephanensis var WSBC in mg/liter were 0.009 and 0.009 (5544 IU each); 0.001 and 0.001 (616 IU each); 0.001 and 0.080 (2.0x107 and 1.6 x 106 spores); and 0.001 and 0.001 (1.3 x 107spores) against adult ticks and eggs, respectively. The value of LC50 against egg stage for Bacillus weihenstephsnensis var KBAB4 was 0.001 mg/liter, and it could not be determined for adult ticks. When LC50 values of these bacterial biocontrol agents were compared with their LD50 values from literature in rats, these bacteria and toxin appeared to be safe for field conditions.
Keywords: Bacterial BCA; Bacillus thuringiensis; Ruminant ticks; LC50